Studi Dramaturgi Presentasi Diri Da’i Migran di Kota Bengkulu - Thadi, Robeet (IAIN Samarinda, 2020)
This paper aims at descriptively revealing the impression management regarding self-presentation of da’i migran (migrant preachers) in Bengkulu that includes: front stage and back stage within the communication process of everyday social life. This research applies qualitative approach within the tradition of dramaturgy. Data were collected through observation, interview and documentation. Findings reveal that the life of migrant preachers that occur in the front stages are very different with those that happened in the back stages. When he/she is in his/her front stages, a migrant preacher is required to act in a distinct manner to match his/her role such as exemplary role, polite in speaking, appropriate and proper in dressings, and live a humble life. In his/her back stage, a migrant preacher is free from such norms since there are no one to watch him/her. Here, a migrant preacher can live his/her take off his/her social mask and can life more authentically because without having to follow the instructions as she/he has to do in the front stage. Keywords: Da'wah activities, dramaturgy, migrant preachers and self-presentation